Math, asked by amisha2805, 1 year ago

solve the equation 2^2x+3 = 65 (2^x-2 ) + 122

Answers

Answered by Sweety2017
6
Maths 1st Rule is Solve Brackets
then BODMAS method , where DMAS is division, multiplication, addition, subtraction are to be solved

(2^x-2)
=2^1 ( means 2raised to 1, written as 2^1 )
=2×1=2

so, 2x-2

now, 2^2x+3
where, 2^2 = 2×2=4
so, 4x+3

Therefore, LHS=RHS
4x+3=65 (2x-2) +122

RHS=65 (2x-2) +122
so brackets to solve now
:.RHS= 130x-130 +122
:RHS= 130x-8

Now,

LHS=RHS
:. 4x+3=130x-8
:. 3+8=130x-4x
.: 11=126x

Now,
x=126/11 (means 126÷11 )
x= 11.45

Thank you :-)

amisha2805: its wrong
amisha2805: in the book its anwser is something else
amisha2805: i think book answer is wrong
amisha2805: thx
Similar questions